The biology of ADGRL4/ELTD1 in angiogenesis and tumour development - Ang, KH (2019)
ADGRL4/ELTD1 is an orphan adhesion G protein-coupled receptor that is expressed in both endothelial cells and vascular smooth muscle cells. ELTD1 expression was significantly upregulated in the tumour vasculature and previous studies in our laboratories identified ELTD1 as a novel regulator of tumour angiogenesis. The aims of this project were to further investigate ELTD1’s in vivo role in the normal and tumour vasculature. In this project, both constitutive and inducible endothelial cell-specific Eltd1 knockout mouse models were generated using Tie2-Cre and Pdgfb-Cre lines respectively. Both models exhibited no significant differences in body and organ weights, or other welfare parameters such as behaviour and movement. There were no observed immunohistochemical differences (CD31 and H&E) in the vital organs namely, brain, heart, lung, liver, kidney and spleen. Interestingly, inducible endothelial cell-specific Eltd1 knockout aortic rings showed inhibition in endothelial cell sprouting that was not observed in the constitutive knockout, suggesting a functional compensatory mechanism in the constitutive model. In both E0771 and MC38 syngeneic tumour models, despite no significant differences in tumour growth curves and survival outcomes, there were observed immunohistochemical differences with generally higher necrosis and hypoxia, and reduction in microvessel density and pericyte coverage in the Eltd1 knockout tumours. Both genetic and drug induced endothelial-Eltd1 deletion gave similar results which affirmed the effects of endothelial-Eltd1 on the tumour vasculature in vivo. Single cell sequencing of acute Eltd1-depleted lung endothelial cells revealed heterogeneity in Eltd1-expressing endothelial cells and showed that lung capillary endothelial cells had higher Eltd1 expression compared to lung arterial endothelial cells. Interestingly, their differential gene expression profiles were distinct. But in both endothelial cell subsets, there were differentially regulated genes whose functions have been associated with endothelial biology, angiogenesis, tumour development and immunology. In summary, endothelial-Eltd1 depletion did not cause toxicity but altered the tumour microenvironment. Therefore, ELTD1 could be considered as a potential target for cancer therapy in combination with other therapies targeting hypoxia and angiogenesis.